Penerapan Aplikasi Accurate Dalam Pencatatan Dan Pelaporan Keuangan Pada PBF PT. Naganusa Putramandiri - Gusman, Salsa Nabila; Nurjanah, Yayuk; Lestari, Febriana Indah; Effendy, Marwan (Jurnal Aplikasi Bisnis Kesatuan, 2024)
The preparation of financial statements is an important thing for any company, so the company should practice good accounting for the finances of its company. In compiling financial statements, companies can begin to take advantage of technological developments by implementing simple accounting applications such as accurate.The purpose of this review is to apply accurate applications in the recording and preparation of a company's financial statements. This observation was carried out by the compiler at Naganusa Putramandiri P.T., based at Veteran No. 52 Bogor Tengah, Bogor City. The observation results showed that Naganuse Putramandi P.P. has not yet prepared the financial report, the company only makes sales records, purchases records, debt records, and company debt payments records. Application of the accurate application to the company begins with preparing the required master data, performing database preparation setup, carrying out the period end process and closing the opening balance. After that, the company can enter the transactions that occur, such as sales, purchases, receipts, debt payments, and other charges payments. The implementation of the accurate application is very beneficial because the company can easily in creating financial reports.   Keywords: financial report, accurate application.